2022
DOI: 10.1113/jp281647
|View full text |Cite
|
Sign up to set email alerts
|

KLB dysregulation mediates disrupted muscle development in intrauterine growth restriction

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Recent studies examining periconceptional maternal exposures suggest that EtOH may impact brain weights in the developing offspring ( Steane et al, 2021 ). Further, increased proportional brain to body weight is a reliable indicator of intrauterine growth restriction (IUGR) ( Cortes-Araya et al, 2022 ). Therefore, we examined the ratio of brain to total bodyweight in the male and female offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies examining periconceptional maternal exposures suggest that EtOH may impact brain weights in the developing offspring ( Steane et al, 2021 ). Further, increased proportional brain to body weight is a reliable indicator of intrauterine growth restriction (IUGR) ( Cortes-Araya et al, 2022 ). Therefore, we examined the ratio of brain to total bodyweight in the male and female offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, there have been many studies on the pathogenesis of IUA, but the role of KLB in this disease has not been clear. Previous studies have shown that KLB is necessary for FGF19 and FGF21 to bind to their homologous receptors with high affinity and is associated with a variety of physiological activities and diseases [ 30 , 31 ]. Immunohistochemistry, immunofluorescence, and Western blot experiments demonstrated that KLB protein is significantly overexpressed in the ESCs of IUA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were differentiated as per a previously published protocol 63 with minor changes. In short, MDPCs (5 × 10 4 ) were seeded in triplicate on rh-Laminin 521 (0.5 µg/cm 2 , Life Technologies)-coated 24-well or 96-well plates plates with growth media (DMEM supplemented with 10% FBS, 5 ng/ml bFGF and 1% PS).…”
Section: Methodsmentioning
confidence: 99%